A concise review of updated global guidelines for the management of hepatocellular carcinoma: 2017-2024 - Hyunjae Shin; Su Jong Yu (Journal of Liver Cancer)
Many guidelines for hepatocellular carcinoma (HCC) have been published and are regularly updated worldwide. HCC management involves a broad range of treatment options and requires multidisciplinary care, resulting in significant heterogeneity in management practices across international communities. To support standardized care for HCC, we systematically appraised 13 globally recognized guidelines and expert consensus statements, including five from Asia, four from Europe, and four from the United States. These guidelines share similarities but reveal notable discrepancies in surveillance strategies, treatment allocation, and other recommendations. Geographic differences in tumor biology (e.g., prevalence of viral hepatitis, alcohol-related liver disease, or metabolic dysfunction-associated steatotic liver disease) and disparities in available medical resources (e.g., organ availability, healthcare infrastructure, and treatment accessibility) complicate the creation of universally applicable guidelines. Previously, significant gaps existed between Asian and Western guidelines, particularly regarding treatment strategies. However, these differences have diminished over the years. Presently, variations are often more attributable to publication dates than to regional differences. Nonetheless, Asia-Pacific experts continue to diverge from the Barcelona Clinic Liver Cancer system, particularly with respect to surgical resection and locoregional therapies, which are viewed as overly conservative in Western guidelines. Advancements in systemic therapies have prompted ongoing updates to these guidelines. Given that each set of guidelines reflects distinct regional characteristics, strengths, and limitations, fostering collaboration and mutual complementarity is essential for addressing discrepancies and advancing global HCC care.